Penggunaan Metode Gerak Dan Lagu Untuk Meningkatkan Kemam-puan Mengenal Angka Pada Anak Kelompok B - Lia Yuliani; Ifat Fatimah Zahro; Ema Aprianti (IKIP Siliwangi, 2026)
This research is motivated by the fact that the ability to recognize the numbers of group B children in Kober Bina Bangsa has not been achieved. Researchers used movement and song methods to solve the problem of recognizing numbers in group B children at the institution. The aim of this research is to determine the increase in the number recognition ability of group B children in Kober Bina Bangsa by using movement and song methods. The research method used is classroom action research (PTK). Classroom action research is research used by teachers in their own classes through self-reflection with the aim of improving their performance as teachers so that children's learning outcomes improve. The subjects of this research were eight children from group B in Kober Bina Bangsa, consisting of three girls and five boys. The data collection technique in this research is observation. Data analysis used qualitative analysis. The steps in this research are planning, acting, observing and reflecting. The conclusion of this research is that, at the pre-cycle stage, children's ability to recognize numbers had not yet reached the very well developed (BSB) category, whereas after the actions in cycle 1 and cycle 2, children's ability to recognize numbers increased and 7 children reached the very well developed (BSB) category.